Photoluminescent Grafted Polymers: Synthesis and Properties of a Polyethylene Matrix Covalently Linked with Porphyrin Units. Issue 13 (24th May 2018) - Rojas‐Montoya, Sandra M.; Vonlanthen, Mireille; Ruiu, Andrea; Rodríguez‐Alba, Efraín; Burillo, Guillermina; Rivera, Ernesto
Abstract: Novel grafted polymers are prepared from commercial low‐density polyethylene (PE) films. First, precursor polymers are synthesized by reacting PE in the presence of acryloyl chloride, using gamma radiation at different radiation doses, to give precursor grafted polymers (PE‐g‐AC). A further esterification reaction between the PE‐g‐AC polymers with a new porphyrin derivative bearing a tetraethylene glycol side chain leads to the formation of novel grafted polymers containing porphyrin units (PE‐g‐AC‐PTEG). These polymers are characterized by Fourier‐transform infrared (FTIR) spectroscopy and their thermal behavior is studied by thermogravimetric analysis and differential scanning calorimetry. The optical properties of the polymers are studied by absorption and fluorescence spectroscopy. In addition, the influence of the irradiation dose on the structure and the optical properties of the polymers is discussed in detail. Abstract : A novel series of grafted polymers are prepared by the modification of commercial polyethylene in the presence of acryloyl chloride, using gamma radiation, with further incorporation of porphyrin chromophores through an esterification reaction. The obtained materials result to be highly luminescent plastics with promising optical applications for the development of sensors and filters.